EDUKASI ZAKAT PENGHASILAN PERTANIAN DAN PERIKANAN BAGI MASYARAKAT PESISIR DESA LAROMABATI, HALMAHERA SELATAN - Muhrim Djakat; Muna Faiza Amatullah; Ramlia Libahongi; Firjan H Kare; Yulnita (LPPM Universitas Abdurrab, 2026)
Coastal communities that depend on the agricultural and fisheries sectors have significant potential for productive zakat; however, literacy regarding agricultural and fisheries zakat remains low, particularly in understanding nisab, rates, calculation methods, and distribution mechanisms. This Community Service Program (PKM) aimed to enhance the understanding and awareness of the people of Laromabati Village, North Kayoa District, South Halmahera, regarding agricultural and fisheries zakat in a contextual and practical manner. The method employed was an educative–participatory approach through interactive lectures, discussions, and pre-test and post-test evaluations involving 25 participants consisting of farmers, fishermen, village officials, and community leaders. The results showed an increase in the average score from 4.5 to 7.6, indicating the effectiveness of the educational intervention in improving productive zakat literacy. Qualitative findings revealed that participants were previously only familiar with zakat al-fitr and had limited understanding of the technical aspects of agricultural and fisheries zakat, particularly in terms of calculation and distribution management. The program recommends follow-up mentoring activities that are more practical in nature, as well as strengthening village-based zakat institutions to support the sustainable implementation of productive zakat practices.